Measure Vient of Consumer Satisfaction - K, Manjunatha (Ushus Journal of Business Management, 2021)
Every human being is a satisfaction maximiser. Satisfaction is the effect of the consumption of the goods and services. Consumer satisfaction is purely subjective phenomenon and an intangible factor and it depends on the consumer state of mind both at the time of purchase and more importantly at the time of consumption. Measurement of consumer satisfaction has been done mostly at superficial level and with certain degree of satisfaction derived by the consumers. Consumer satisfaction with respect to edible oils is operationally defined as the degree to which a consumer fulfills His/Her needs and expectations from the edible oils. An attempt is made in this study to measure the consumer satisfactipn with special reference to edible oil consumption.